Immunized Goat with a Conjunctival Vaccine Prevent the Abortus Despite Revaccination with the Same Strain. (March 2022) - Meglia, G.; Castillo, M.; Cerutti, D.; Gomez, M.B.; Tortone, C.; Gastaldo, M.; Elena, S.; Ardoino, S.; Franco, C.; Bagnat, E.
Abstract : Purpose: Brucellosis is a zoonotic disease, endemic in certain areas of Argentina, affecting small ruminant's health but, with insidious effect on the smallholder's family, especially women and children. Blind vaccination with Rev-1 strain vaccine stops the direct and simultaneous transmission of the disease. Primo-vaccination of prepuberal does with the strain Rev-1 immunize against the disease, caused by Brucella melitensis, and did not affect the future gestation, but when the primo-vaccination occurs during mid-gestation (50 to 120 days) the aforementioned strain produces a high number of abortus. Therefore, the project aimed to assess if the primo-vaccinated goats with the Rev-1 vaccine protect them, when they were revaccinated during gestation. Methods & Materials: Twenty-two brucellosis-free Boer does were evenly assigned to one of two groups, either yellow (Yg, n=11) or red (Rg, n=11) groups, according to ear tag colour. Yg received two conjunctival REV-1 doses, 20 days before and at 95 days of the beginning of the natural mating whereas, Rg just received one dose at 98 days of the start of the natural mating. Blood samples were taken at five time points to evaluate the humoral immune response, and microbiological samples were held at either calving or abortion. Serum immunoglobulins were assessed by Buffered Plate Agglutination Test (BPA) and confirmed by Fluorescent Polarization Assay (FPA) whereas, microbiology samples were seed in Farrel medium and confirmed by PCR (Bruce-ladder). Results: The pregnancy percentage was 82 and 91% at the Y and Rg, respectively. Yg goats delivered full-term healthy kids whereas, the Rg, out of 10 pregnant goats, two delivered premature kids and eight abortuses. Brucella Rev-1 strain was isolated from both the abortus foetuses and the mothers' vaginal swabs of the Rg on the day of parturition and at 5 days after whereas, the Yg goats delivered healthy kids and the vaginal swabs resulted in microbiology negative Conclusion: In conclusion, the immunity induced in the Yg by the primo-vaccination protected them significantly (p<0, 0001) against the abortus in face of defy with revaccination whereas, the Rg (control), without primo-vaccination but with the same pregnancy condition and revaccination challenge aborted 80% of the goats.